KONSEP BELAJAR PERSEPEKTIF IMAM AL-GHAZALI DALAM BUKU AYYUHAL WALAD FI NASIHATI AL-MUTA'ALLIMĪN MAW'IZATIHIM LIYA'LAMŪ WA YUMAYYIZŪ 'ILMAN NĀFI'AN MIN GHAYRIH - Hepi Ikmal; Maskan Maskan (Akademika, 2017)
Humans will not be able to utilize the natural resources such as land and sea, without armed with knowledge that qualified. Therefore, Islam then obliges Muslims to seek knowledge or learning. Learning could be capable of building a civilization. On this stand, the writer wants to discuss the thesis titled "Learning Perspectives Imam Al-Ghazali in the Book Ayyuhal Walad Fi Nasihati Al-Muta'allimīn Maw'izatihim Liya'lamū Wa Yumayyizū 'Ilman Nāfi'an Min Ghayrih." The formulation of the problem is how to learn the perspective of Imam Al-Ghazali in the book Ayyuhal Walad. The purpose of this study was to determine the learning perspective of Imam Al-Ghazali in the book Ayyuhal Walad, to determine the factors that determine the success of the learning process perspective Imam Al-Ghazali in the book Ayyuhal Walad. It is as library research using qualitative descriptive approach to critical analysis. The results of the study is the approach filled with shades theocentric. The factors that determine the success of the learning process perspective Imam Al-Ghazali in the book Ayyuhal Walad is the motivating factor, educators, curriculum, student attitudes, purity of heart, of environmental social.Keywords: Learning, Imam Al-Ghazali